2021
DOI: 10.32539/bsm.v5i7.391
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Health Protocol and Religious Activities: Knowledge, Attitude, and Compliance among Generation Z

Abstract: Background: COVID-19 (coronavirus disease 2019) is a contagious infection currently affecting people worldwide, including in Indonesia. The spread of this virus is extremely rapid, and the number of deaths continues to rise. Compliance with the health protocol is one method of preventing the spread of COVID-19. The purpose of this study is to determine the relationship between generation-Z (gen-Z) knowledge and attitudes toward the use of masks, keeping distance, and washing hands as a means of preventing COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The findings of this study indicate that if the community has a good understanding of how to prevent Covid-19, it will comply with health protocol implementation. The findings of this study are consistent with the findings of previous studies conducted by Ramayanti et al, (2021) on the Relationship between Knowledge, Attitudes of Gen Z, and Compliance in Revealing the Covid-19 Health Protocol in Religious Activities in the City of Palembang, which found a significant relationship (pvalue <0,05) between Generation Z's knowledge about Covid-19 and adherence to using masks (p-value=0,001), keeping your distance (p-value=0,002), and hand washing.…”
Section: Table 2 the Relationship Between Generation X's Education Le...supporting
confidence: 93%
“…The findings of this study indicate that if the community has a good understanding of how to prevent Covid-19, it will comply with health protocol implementation. The findings of this study are consistent with the findings of previous studies conducted by Ramayanti et al, (2021) on the Relationship between Knowledge, Attitudes of Gen Z, and Compliance in Revealing the Covid-19 Health Protocol in Religious Activities in the City of Palembang, which found a significant relationship (pvalue <0,05) between Generation Z's knowledge about Covid-19 and adherence to using masks (p-value=0,001), keeping your distance (p-value=0,002), and hand washing.…”
Section: Table 2 the Relationship Between Generation X's Education Le...supporting
confidence: 93%
“…The next influential psychological factors in the regression analysis were belief about time (attitude) and action control (self-regulation). A previous study that was conducted in the pandemic situation indicated a significant relationship between attitudes about COVID-19 and health protocols [ 43 ]. Attitude is crucial because it influences behavior and actions, e.g., action control .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on exploring and defining the concept of Unconventional Religious Orientations in depth, with special attention to the specific group of Generation Z [1,2]. Generation Z, usually referred to as the younger generation born between 1995 and 2010, has grown up in a unique socio-cultural environment characterized by In exploring this phenomenon, it is important not to lose sight of the influence of the particular cultural context of China.…”
Section: Introductionmentioning
confidence: 99%